The Relationship between the duration of DMPA injection contraceptive use and menstrual disorders: Hubungan Lama Penggunaan Kb Suntik DMPA dengan Gangguan Mesntruasi - Dwi Astuti, Novi; Maineny, Arie; Jesdika Longulo, Olkamien; Sumiaty; Widyayanti, Asri; Suryani, Sindi (Napande: Jurnal Bidan, 2024)
Background: The relationship between the use of contraception and menstrual disorders, data from the Pantoloan health center in Palu City in 20232 as many as 2,157 WUS who use DMPA contraception, Family planning is an effort to minimize or plan the number and distance of pregnancies with. Objective: to determine the relationship between the use of DMPA injectable contraceptives with menstrual disorders in birth control acceptors at the Pantoloan Health Center in 2023. The method used was case-control with a retrospective population in this study, which was 2,157 EFAs in the Pantoloan Health Center area of Palu City. With a sample of 96 respondents, data collection techniques came from primary data and secondary data with univariate and bivariate types of analysis, while the sampling technique in this study was purposive sampling. This research has been carried out from August 30, 2023. This study used a parametric test with the Chi-square Test using SPSS. The results of 96 respondents who experienced menstrual disorders were 65 PUS, so in this study, there is a relationship between the use of DMPA injectable birth control with menstrual disorders at the Pantoloan Health Center. Conclusion There is a relationship between the duration of use and menstrual disorders. Researchers hope to improve the quality of service, provision of information, and education on the selection of the right family planning for PUS.